2009
DOI: 10.2519/jospt.2009.3002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitivity of the Lower Extremity Nervous System During Straight-Leg Raise Neurodynamic Testing in Healthy Individuals

Abstract: respond to the mechanical stresses imposed upon them during movement. 27 Neurodynamic tests are used to assess the nervous system's mechanosensitivity through monitoring the response to movements that are known to alter the mechanical stresses acting on the nervous system. The most common lower quarter neurodynamic test is the passive straight-leg raise (SLR) test. 13,31 The basic SLR test consists of the tester performing passive hip flexion, with the patient in a supine position and the knee held in full ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
118
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 35 publications
6
118
1
3
Order By: Relevance
“…11,[21][22][23] According to Nee and Butler (2006), cited in Boyd et al, 24 the criteria for interpretation of neurodynamic testing include whether the test (a) reproduces the symptoms, (b) identifies a significant deviation from normal, or (c) produces alterations in the symptoms by adding in a distal joint movement, also called sensitizing movements. 24 For example, muscle EMG activity, location of symptoms, and hip motions are altered when performing 2 sensitizing versions of the straight leg raise maneuver, assisting clinicians to Fig 3. A, Proximal slider, a straight leg raise and application of plantar-flexion without producing symptoms. B, Distal slider; during the phase in which the leg is flexed, the foot is dorsiflexed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,[21][22][23] According to Nee and Butler (2006), cited in Boyd et al, 24 the criteria for interpretation of neurodynamic testing include whether the test (a) reproduces the symptoms, (b) identifies a significant deviation from normal, or (c) produces alterations in the symptoms by adding in a distal joint movement, also called sensitizing movements. 24 For example, muscle EMG activity, location of symptoms, and hip motions are altered when performing 2 sensitizing versions of the straight leg raise maneuver, assisting clinicians to Fig 3. A, Proximal slider, a straight leg raise and application of plantar-flexion without producing symptoms. B, Distal slider; during the phase in which the leg is flexed, the foot is dorsiflexed.…”
Section: Discussionmentioning
confidence: 99%
“…detect meaningful clinical differences in relation to tension in the neural structures. 24,25 It has been postulated that NM may produce its effects by increasing axoplasmic flow, improving intraneural swelling, and reducing pressure and inflammation in neural tissue. 26,27 In addition, previous studies have demonstrated that neural provocation tests produce statistically significant increases of muscle activity compared to resting levels in the upper and lower limb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the possible links between anterior knee pain and deficits in lower extremity muscle strength and flexibility, and the potential impact of muscle activation and flexibility problems on the results of neurodynamic testing, 1,4,13,15,16 a series of physical examinations for lower extremity flexibility, strength, and alignment, as well as functional testing and the general ligamentous laxity test, were conducted. This ensured that lower extremity flexibility or strength did not interfere with the results of the FST.…”
Section: Methodsmentioning
confidence: 99%
“…2,13 To determine whether neurodynamic responses contribute to the occurrence of clinical symptoms, a structure differential maneuver, such as neck flexion/extension, could be added to further change the stress on the neural tissues in question, while minimizing the movement of the musculoskeletal tissues in the target region. 1,[2][3][4]10,15 In patients, the T T STUDY DESIGN: Matched-control, crosssectional study.…”
mentioning
confidence: 99%